Does the integration of enviromental impact assessment and mine closure planning deliver effective mine closure plans in Western Australia? - Getty, R.; Morrison-Saunders, A. (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
Environmental impact assessment (EIA) and mine closure planning became formally integrated in Western Australia in 2011 when amendments to the Mining Act 1978 resulted in the requirement of a mine closure plan (MCP) to be submitted by proponents along with their EIA documents. This procedural innovation aimed to force early consideration of mine closure in line with international best practice and raise the level of closure planning compliance. Internationally, it is generally held that early closure planning will reduce costs and improve closure outcomes thereby reducing financial, environmental and social liabilities. This paper presents the results of the first study to explore the integration of EIA and mine closure planning in Western Australia and consider the extent to which such integration facilitates effective MCPs at the project approval stage. The opinions of twelve experienced EIA and/or mine closure professionals, representing regulators and proponents alike, were obtained from semi-structured interviews. Thematic analysis used both top down and bottom up approaches to identify recurring themes and novel concepts. Overall both regulators and proponents were found to be strongly supportive of the integration of EIA and the potential of early planning to improve mine closure outcomes, particularly with regard to the identification and reduction of risk. However, opinions were divided about the influence of integration on the effectiveness of early MCP or if the current Western Australian ‘Guidelines for Preparing Mine Closure Plans’ are capable of delivering effective early MCP. The responses suggest that although the current regulatory framework exists to drive integration that could enable effective MCP at the project assessment and approval stage, the most important factor is the motivation of key facilitators to pursue good outcomes. Opportunities to enhance the current framework lie in increasing transparency, expanding aspects of the guidance and ensuring enforcement of the commitments made in mine closure plans.